2019
DOI: 10.3390/cells8080914
|View full text |Cite
|
Sign up to set email alerts
|

Functions and the Emerging Role of the Foetal Liver into Regenerative Medicine

Abstract: During foetal life, the liver plays the important roles of connection and transient hematopoietic function. Foetal liver cells develop in an environment called a hematopoietic stem cell niche composed of several cell types, where stem cells can proliferate and give rise to mature blood cells. Embryologically, at about the third week of gestation, the liver appears, and it grows rapidly from the fifth to 10th week under WNT/β-Catenin signaling pathway stimulation, which induces hepatic progenitor cells prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 118 publications
(194 reference statements)
0
23
0
Order By: Relevance
“…Immortalized cells were cultured in Opti-MEM medium supplemented with 10% FBS. In order to determine the HPC population, we compared the corresponding mRNA expression profile of genes encoding (1) HPCs and hepatic specific markers, such as α-fetoprotein ( AFP ), hepatocyte nuclear factor 4 α ( HNF4A ), and alanine aminotransferase ( ALAT ) [21]; (2) HPCs and cholangiocyte-specific markers ( SOX9 ) [22] and epithelial cell adhesion molecule ( EPCAM ) [16]; (3) adipose-derived mesenchymal stem cell (ASCs) markers, such as CD105 and CD90 [23]; as well as an endothelial cell specific marker, platelet and endothelial cell adhesion molecule 1 ( PECAM1 ) [24]. We found that similarly to whole liver tissue, cultured HPCs expressed HNF4A and ALAT.…”
Section: Resultsmentioning
confidence: 99%
“…Immortalized cells were cultured in Opti-MEM medium supplemented with 10% FBS. In order to determine the HPC population, we compared the corresponding mRNA expression profile of genes encoding (1) HPCs and hepatic specific markers, such as α-fetoprotein ( AFP ), hepatocyte nuclear factor 4 α ( HNF4A ), and alanine aminotransferase ( ALAT ) [21]; (2) HPCs and cholangiocyte-specific markers ( SOX9 ) [22] and epithelial cell adhesion molecule ( EPCAM ) [16]; (3) adipose-derived mesenchymal stem cell (ASCs) markers, such as CD105 and CD90 [23]; as well as an endothelial cell specific marker, platelet and endothelial cell adhesion molecule 1 ( PECAM1 ) [24]. We found that similarly to whole liver tissue, cultured HPCs expressed HNF4A and ALAT.…”
Section: Resultsmentioning
confidence: 99%
“…The sole treatment available is using human umbilical cord mesenchymal stem cell-derived extracellular vesicles, but these have potential tumorigenic effects or trigger cancer in a patient through upregulating the Bcl‐2 oncogene or activating ERK1/2 phosphorylation [ 26 ]. The findings of the presents study will help the liver transplant surgeons to understand the cytoarchitecture of foetal liver and future researchers working on hepatic tissue engineering [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, during the 5-6 th week of gestation (10 mm embryo) the human fetal liver is colonized by hematopoietic progenitors, and by the 2 nd trimester of gestation approximately 60-70% of the hepatic parenchyma is populated by hematopoietic cells [7] (Figure 1a). Additionally, the fetal liver has often been described as a "cardiovascular tissue" [8], since it receives oxygenrich blood from the umbilical vein and shunts it via the ductus venosus to the inferior vena cava and then to the fetus's heart. Fetal hepatic metabolism is also incapable of matching adult levels.…”
Section: Liver Development and Remodeling After Birthmentioning
confidence: 99%